(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The relative advantage and the gift of source are not longer enough to execute the international exchange .However, there are group of determinants must be taken to create competitive advantage, which are the basic to perform the international exchange .Therefore, the developing countries which seek to achieve progress and development have to take in account these determinants in order to promote the competitive ability into international market .